Optimal dynamic scale and structure of a multi-pollution economy - Baumgärtner, Stefan; Jöst, Frank; Winkler, Ralph (Ecological economics, 2009)
We analyze the optimal dynamic scale and structure of a two-sector-economy, where each sector produces one consumption good and one specific pollutant. Both pollutants accumulate at different rates to stocks which damage the natural environment. This acts as a dynamic driving force for the economy. Our analysis shows that along the optimal time path (i) the time scale of economic dynamics is mainly determined by the lifetime of pollutants, their instantaneous harmfulness and the discount rate; (ii) economic scale and structure, as well as resulting welfare, may be non-monotonic, and (iii) environmental damage may exhibit an inverted U-shape form. These results raise important questions about the optimal design of environmental policies in a multi-pollution economy. We suggest a system of dynamic Pigouvian emission taxes, each of which should be levied specifically on one particular pollutant. We show that the optimal time path of each tax level is determined by the characteristics not only of that particular pollutant but also of all other pollutants.